DataPublics The Construction of Publics in Datafied Democracies - Hartley, Jannie Møller; Sørensen, Jannick Kirk; Mathieu, David (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Drawing on empirical data from US and UK as well as the unique example of Nordic countries where there is a high level of confidence in state and media institutions, this book shows how platforms and algorithms are transforming media, journalism and audiences' civic practices today.